2020
DOI: 10.1371/journal.pone.0232274
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterization of flavivirus production in two cell lines: Human hepatoma-derived Huh7.5.1-8 and African green monkey kidney-derived Vero

Abstract: The Flaviviridae is a family of enveloped viruses with a positive-sense single-stranded RNA genome. It contains many viruses that threaten human health, such as Japanese encephalitis virus (JEV) and yellow fever virus (YFV) of the genus Flavivirus as well as hepatitis C virus of the genus Hepacivirus. Cell culture systems highly permissive for the Flaviviridae viruses are very useful for their isolation, propagation, and diagnosis, an understanding of their biology, and the development of vaccines and antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For instance, C6/36 cells exhibit altered RNA-mediated antiviral immunity ( Brackney et al, 2010 ; Scott et al, 2010 ). Huh7.5.1 cells are RIG-I-deficient ( Shirasago et al, 2015 ; Zhong et al, 2006 ) while Vero cells are deficient in type-I interferon production ( Saito et al, 2020 ; Desmyter et al, 1968 ; Osada et al, 2014 ). Intriguingly, viral populations exhibit an intermediate phenotype in Huh7.5.1 cells relative to the other primate and insect cell lines, which are distinct from their phenotype in Vero cells.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, C6/36 cells exhibit altered RNA-mediated antiviral immunity ( Brackney et al, 2010 ; Scott et al, 2010 ). Huh7.5.1 cells are RIG-I-deficient ( Shirasago et al, 2015 ; Zhong et al, 2006 ) while Vero cells are deficient in type-I interferon production ( Saito et al, 2020 ; Desmyter et al, 1968 ; Osada et al, 2014 ). Intriguingly, viral populations exhibit an intermediate phenotype in Huh7.5.1 cells relative to the other primate and insect cell lines, which are distinct from their phenotype in Vero cells.…”
Section: Resultsmentioning
confidence: 99%
“…It was investigated by plaque inhibition assay after the determination of its cytotoxic activity on Vero-E6 cells. These cells are derived from the kidney of an African green monkey and they are widely used in virology studies [28]. APEE exhibited potent antiviral activity against SARS-CoV-2 in Vero-E6 cells with a value of IC 50 1.1 ± 0.03 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we resequenced the genomic DNA from Huh7 and Huh7.5.1-8 using a Sanger sequencer and verified that the mutation is absent in Huh7 but heterozygous in Huh7.5.1-8 ( Figure 2). Our recent study showed that a 55T allele transcript harbors an allele-specific large deletion and, presumably, nonfunctional in Huh7.5.1-8 (Saito et al, 2020). The results showed that, although T55I mutation is heterozygous in the Huh7.5.1-8 genome, all full-length RIG-I proteins have the T55I mutation.…”
Section: Missense Mutation In Rig-i (T55i) Wasmentioning
confidence: 97%